Evaluasi Dampak Soft Skill Dan Hard Skill Terhadap Profesionalisme Guru PAI di SMP IT NW Teko - Komarudin; Zainul Arifin; Welly Kuswanto (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
This study evaluates the impact of soft skills and hard skills on the professionalism of Islamic Religious Education (PAI) teachers at SMP IT NW Teko. The issue is important because PAI teacher professionalism is shaped not only by subject-matter mastery but also by teachers’ ability to build educational relationships, guide character development, manage classrooms, and adapt to learning technology. The study employed a qualitative case study design. Data were collected through classroom observation, semi-structured interviews with the principal, PAI teachers, peer teachers, and students, and document analysis of lesson plans and teacher development activities. Data were analyzed thematically through data reduction, theme construction, data display, and conclusion drawing. Trustworthiness was strengthened through source triangulation, technique triangulation, cross-data consistency checks, and researcher reflexivity. The findings show that soft skills affect the development of trust, warm communication, more humane discipline, and moral guidance that is closer to students’ lived experiences. Hard skills affect teachers’ readiness to design instruction, master learning materials, use digital media, develop assessment tools, and identify follow-up learning needs. The synergy between both skill sets shapes holistic PAI teacher professionalism: pedagogically and technically competent, personally mature, and socially-spiritually grounded. The contribution of this article lies in demonstrating that the evaluation of PAI teacher professionalism should read the impact of soft skills and hard skills integratively rather than separately. Practically, schools need to strengthen teacher development through training, reflective supervision, peer mentoring, and continuous digital literacy enhancement.